2016
DOI: 10.1111/voxs.12272
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell genotyping in China

Abstract: The common antigens of ABO, Rh, MNS, Duffy, Kidd, Diego, Yt and Dombrock blood group systems have a polymorphic distribution in the Chinese population. The Mur antigen and anti‐Mur are more common in the Chinese Han and some minority groups in the southern region of China. Except for the common ABO alleles (A101, A102, B101, O01 and O02), more than 100 new alleles have been reported in the Chinese population, in which the effect of many critical mutations on the variant expression of A and B antigens still nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…The improved resolution in RHD genotyping strategy has allowed a diverse array of RHD variants beyond RHD*weak D type 1, RHD*weak D type 2 and RHD*weak D type 3 to be defined. This included East Asianassociated RHD variants such as RHD*weak partial 15 and RHD*weak D type 33, and African-associated variants such as RHD*weak partial 4Á0, RHD*weak partial 4Á1 and RHD*weak D type 90 [7,[22][23][24][25][26][37][38][39]. It also included a novel RHD*c.939+3A>C variant that had exhibited a nucleotide substitution in Intron 6 and a weak partial D-epitope profile lacking epD1Á2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improved resolution in RHD genotyping strategy has allowed a diverse array of RHD variants beyond RHD*weak D type 1, RHD*weak D type 2 and RHD*weak D type 3 to be defined. This included East Asianassociated RHD variants such as RHD*weak partial 15 and RHD*weak D type 33, and African-associated variants such as RHD*weak partial 4Á0, RHD*weak partial 4Á1 and RHD*weak D type 90 [7,[22][23][24][25][26][37][38][39]. It also included a novel RHD*c.939+3A>C variant that had exhibited a nucleotide substitution in Intron 6 and a weak partial D-epitope profile lacking epD1Á2.…”
Section: Discussionmentioning
confidence: 99%
“…Weak D types 4Á0 and 4Á1 have been reported as frequently occurring alleles in African populations from Egypt, Tunisia, Ethiopia and South Africa [7,21,22]. Weak D type 15 and 33 predominate in East Asian donor populations from Japan, China and Taiwan [23][24][25][26]. In 2000, a study of 99 Australian blood donors with a weak D phenotype showed the majority of RHD variants comprised weak D types 1, 2 or 3 (n = 88), similar to those reported in Europe and Canada [27].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption/elution testing for the serological identification of the DEL phenotype is not routinely conducted in China, with the result that individuals with DEL phenotype are always treated as having a D− phenotype. The RHD*01N.03 [ RHD*CE(2‐9)‐D ] hybrid allele is the most common non‐functional allele accounting for the D− phenotype in the Chinese population, while RHD*weak partial 15 and RHD*DVI.3 are the most frequent alleles, accounting for more than 70% of the reported Chinese D variant probands . In this study, the RHD genotype and its zygosity were analysed in the D+, D− and D variant donors using the developed RH ‐MLPA genotyping assay in the Chinese Southern Han donors.…”
Section: Introductionmentioning
confidence: 99%
“…This example also indicates East Asian‐specific antigens, especially Di a ‐ and Mur‐positive cells, should be involved in the antibody screening cells for routine testing in East Asian population. Di a and Mur antigens distribute with a frequency of 2‐8% and 0·5–24·7% in the Chinese population from the mainland of China and anti‐Mur is one of most common alloantibodies identified in the population from the southern region of China . When reagent RBCs used for antibody screening represent an antigen profile suited for investigation in the Caucasian population, detection of antibodies clinically significant in the Asian population may be missed.…”
Section: Comprehensive Genotyping For the Blood Group Antigens In Thementioning
confidence: 99%